Brown algae potential as a functional food against hypercholesterolemia: review - André, Rebeca (2021)
Brown algae have been part of the human diet for hundreds of years, however, in recent years, commercial and scientific interest in brown algae has increased due to the growing demand for healthier diet by the world population. Brown algae and its metabolites, such as carotenoids, polysaccharides, phlorotannins, and proteins, have been associated with multiple beneficial health effects for different diseases, such as cardiovascular diseases, one of the main causes of death in Europe. Since high blood cholesterol levels are one of the major cardiovascular risks, this review intends to provide an overview of current knowledge about the anti-hypercholesterolemic effect of different brown algae species and/or their isolated compounds.